2008 19th International Conference on Database and Expert Systems Applications 2008
DOI: 10.1109/dexa.2008.70
|View full text |Cite
|
Sign up to set email alerts
|

Particle Swarm Optimization Using Adaptive Mutation

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…Pant [8] used an adaptive mutation operator in PSO, which was based on the idea of FEP. The particles are mutated at the end of each iteration according to the following rule:…”
Section: B Pso With Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pant [8] used an adaptive mutation operator in PSO, which was based on the idea of FEP. The particles are mutated at the end of each iteration according to the following rule:…”
Section: B Pso With Mutationsmentioning
confidence: 99%
“…When a particle has no change in a fixed number of generations, the particle should jump to a new point by adding a random number generated by Cauchy distribution. Pant [8] used an adaptive Cauchy mutation operator in PSO, which was based on the idea of FEP. Chen [9] presented a Gaussian mutation operator with adaptive mutation probability.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that has shown that PSO can outperform generic algorithm for difficult problem classes [6], [7], [8]. Many successful applications of the PSO algorithm have been reported for solving biological problems [9], [10], [11] and numerous improvements to the algorithm have been proposed [12], [13], [14], [15], [16], [17], [18], [19], [20]. Refer to [21], [22] for reviews of PSO.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently they investigate several mutation operators (Cauchy, Gaussian and Levy mutation) based on the global best particles, an adaptive mutation operator is then formulated by integrating the three mutation operators described above together at different stages for the best optimization performance [8]. In the meanwhile, Pant et al [9] present two variants of PSO with adaptive mutation, in which both the personal best position and the global best swarm position are mutated by Beta distribution respectively. In addition, the opposition-based learning algorithm is introduced into PSO as so to accelerate the learning and searching process [10], in which the mutation threshold is automatically adapted in terms of the evolutionary information of the global best particles.…”
Section: Introductionmentioning
confidence: 99%